PENINGKATAN KEMAMPUAN MOTORIK HALUS ANAK MELALUI PERMAINAN PAPAN PASAK KARET GELANG DI PAUD MAWADDAH KOTA PADANG PANJANG - Febrida S. (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2015)
The background of this research is the lack of children‟s ability to perform about the fine motor skills activities. This research was purposing in illustrate the increasing of the fine motor skills of children in the movement of finger flexibility, about hands and eye coordination, also about the speed of movement of the hand fingers. The subject of this research is a class action research based on group B Mawaddah early childhood students which held on fifteen kids. The data collection technique that used in this research is the data analysis technique by using percentage. And the results showed that the elastic band on peg board games can improve fine motor skills in the finger movements spasticity of the fingers, hand and eye coordination, the speed of fingers movements, both in the first siclus and the second siclus. The suggestions of the research are to expected the parents and teachers to be able to use rubber bands peg board games, and the next researchers can conduct the research subject on other aspects progression by using different methods in order to improve fine motor skills of a child.